EXPLORING DIFFICULTIES IN TEXTUAL UNDERSTANDING OF MATHEMATICAL WORD PROBLEMS FROM A PSYCHOLINGUISTIC PERSPECTIVE AND USE OF DRAWINGS - Reyes-Huerta, Valentín; Juárez-López, José Antonio; Iglecias-Antonio, Reynaldo (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Several studies have reported the importance of textual understanding in the solving of verbal mathematical problems. Therefore, the objective of the present study was to analyze the difficulties the secondary-education students presented in the textual understanding of verbal mathematical problems. An instrument was applied with three verbal problems in three different moments: comprehension of the problem, representation of the situation, and the application of a semi-structured interview. An important factor that could be seen in the responses obtained is that the context played an essential role. It was also obtained that the textual understanding and the cultural context show an important relationship when building a representation of the problem. Finally, according to the results obtained in the study, we suggest that it would be important to encourage students to do previous work to familiarize themselves with the context posed in the problem to be able to reach a solution that satisfies the statement.